Stand-alone totally thoracoscopic left atrial appendage exclusion using a novel clipping system in patients with high risk of stroke – initial experience and literature review - Suwalski, Piotr; Witkowska, Anna; Drobiński, Dominik; Rozbicka, Joanna; Sypuła, Sławomir; Liszka, Irena; Smoczyński, Radosław; Staromłyński, Jakub; Walecka, Irena; Kosior, Dariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : Atrial fibrillation (AF) is the most common clinically relevant arrhythmia and it is strongly associated with stroke. Left atrial appendage (LAA) is considered to be the most often source of thrombotic material. In recent decades a number surgical, percutaneous and hybrid approaches for LAA occlusion have been described revealing very different level of success and showing a variety of challenges associated with this matter. We present the first Polish experience with the stand-alone totally thoracoscopic LAA exclusion using novel clipping system. Material and methods : Four patients (one male) in mean age of 74 (± 13) years with long-standing persistent and chronic AF were admitted for totally thoracoscopic LAA exclusion. All patients had significant comorbidities and the history of the oral anticoagulation intolerance or suboptimal/unstable level (CHA2DS2-VASC > 5, HAS_BLED > 3). Three procedures were performed through totally thoracoscopic access. In one patient due to massive adhesions in the left pleura we performed minithoracotomy in fourth left intercostal space. In two months follow-up we observed no mortality, no strokes and no bleedings. Results : In all patient total exclusion of LAA with no residual remnant was confirmed. The “skin-to-skin” procedural time took on average 40, minimum 20 minutes. Patients were extubated directly or within two hours after procedure. All patients were discharged early in a good condition. Conclusions : Our initial first experience with the novel totally thoracoscopic clipping system for stand-alone LAA exclusion is very promising showing very high efficacy and good safety profile.